Preserving Food: Freezing Vegetables - Judy A. Harrison; Elizabeth Andress; Amy Simonne (EDIS)
Freezing is an excellent way to preserve fresh vegetables at home. Freezing does not sterilize food; the extreme cold simply retards growth of microorganisms and slows down changes that affect quality or cause spoilage in food. The quality of frozen vegetables depends on the quality of the fresh products and how they are handled from the time they are picked until they are ready to eat. It is important, also, to start with high-quality vegetables because freezing will not improve the product's quality. This document is Fact Sheet FCS 8768, a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: August 2004.